Development of live pharmacies in association with brazilian sociodemographic factors (Research, Society and Development, 2022)
The aim of this study was to analyze the implementation of the National Policy on Medicinal Plants and Herbal Medicines in the Brazilian Unified Health System through Live Pharmacies. The methodology consists of a descriptive documental and bibliographic research, based on a search for journal articles, books, survey of official normative documents, in databases such as the Capes/MEC Journal Portal, PubMed, Scielo, Academic Google, Ministry of Health portal, Official Gazette of the Union, official website of the health secretariats, Anvisa and IBGE. In the period between March 2020 and October 2020. For a survey of actions, public and regulatory policies in the scope of medicinal and herbal plants, regulations were sought between 1982 and 2009. The period from 1983 to 2020 was considered for analysis of the institutionalization of Living Pharmacies. In relation to public resources, notices were considered in the period from 2012 to 2020; and for sociodemographic data, the period from 2012 to 2020 was retrieved, with the publications of the Ministry of Health. As a result, it is observed that actions, public and regulatory policies contributed to the expansion of medicinal plants and phytotherapy programs by the Brazil, and the Live Pharmacies within the scope of the SUS. It was concluded that the financial resources were made available with regularity and specific destination, but distributed unevenly, considering the regional sociodemographic needs. Greater financial support would be needed for regions with greater socio-economic vulnerability, reducing bureaucracy in accessing resources, and strengthening regional public policies.